Clifford the firehouse dog - Bridwell, Norman (New York : Scholastic, 1994)
When Emily Elizabeth and Clifford visit Clifford's brother, Nero, a fire rescue dog, Clifford demonstrates fire safety and helps to put out a fire.
J
In logo on cover: Clifford, the big red dog.
b
b
Keywords: Dogs -- Fiction; Fire extinction -- Fiction